Renal denervation in patients with versus without chronic kidney disease: results from the Global SYMPLICITY Registry with follow-up data of 3 years - Ott, Christian; Mahfoud, Felix; Mancia, Giuseppe; Narkiewicz, Krzysztof; Ruilope, Luis M.; Fahy, Martin; Schlaich, Markus P.; Böhm, Michael; Schmieder, Roland (Nephrology Dialysis Transplantation, 2022)
BACKGROUND: Activity of the sympathetic nervous system is increased in patients with hypertension and chronic kidney disease (CKD). Here we compare short- and long-term blood pressure (BP)-lowering effects of renal denervation (RDN) between hypertensive patients with or without CKD in the Global SYMPLICITY Registry. METHODS: Office and 24-h ambulatory BP (ABP) were assessed at prespecified time points after RDN. The presence of CKD was defined according to the estimated glomerular filtration rate (eGFR) and enrolled patients were stratified based on the presence (n = 475, eGFR <60 mL/min/1.73 m2) or absence (n = 1505, eGFR ≥60mL/min/1.73 m2) of CKD. RESULTS: Patients with CKD were older (P < 0.001) and were prescribed more antihypertensive medications (P < 0.001). eGFR decline per year was not significantly different between groups after the first year. Office and 24-h ABP were significantly reduced from baseline at all time points after RDN in both groups (all P < 0.001). After adjusting for baseline data, patients without CKD had a greater reduction in office systolic BP (-17.3 ± 28.3 versus -11.7 ± 29.9 mmHg; P = 0.009) but not diastolic BP at 36 months compared with those with CKD. Similar BP and eGFR results were found when the analysis was limited to patients with both baseline and 36-month BP data available. There was no difference in the safety profile of the RDN procedure between groups. CONCLUSIONS: After adjusting for baseline data, 24-h systolic and diastolic ABP reduction were similar in patients with and without CKD after RDN, whereas office systolic but not diastolic BP was reduced less in patients with CKD. We conclude that RDN is an effective antihypertensive treatment option in CKD patients.
CRIS-Team Scopus Importer:2022-02-11
Keywords: blood pressure; hypertension; renal function